Analisis Strategi Pemasaran Ayam Geprek di Kota Bekasi - Puspita, Ayu Diah; Yunita, Tyna (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
In a competitive business environment, SMEs in the city of Bekasi continue to grow. Established in 2015, Ayam Geprek must choose the best marketing plan to compete. This study uses SWOT analysis and qualitative descriptive research methods to identify the best marketing strategy for Ayam Geprek in Bekasi. Thirty questions were used to collect research data on the fried chicken company from primary and secondary sources, each reflecting variables of strengths, weaknesses, opportunities, and threats. Based on the results, the fried chicken company falls into Quadrant I and supports aggressive initiatives with an internal strength score of 1.4 and an environmental opportunity score of 0.8. The strategies implemented are product creation and innovation strategies, market entry strategies, market expansion, and integration.